2017
DOI: 10.3945/an.116.014605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics on Necrotizing Enterocolitis, Sepsis, Intraventricular Hemorrhage, Mortality, Length of Hospital Stay, and Weight Gain in Very Preterm Infants: A Meta-Analysis

Abstract: Probiotics are increasingly used as a supplement to prevent adverse health outcomes in preterm infants. We conducted a systematic review, meta-analysis, and subgroup analysis of findings from randomized controlled trials (RCTs) to assess the magnitude of the effect of the probiotics on health outcomes among very-low-birth-weight (VLBW) infants. Relevant articles from January 2003 to June 2017 were selected from a broad range of databases, including Medline, PubMed, Scopus, and Embase. Studies were included if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 55 publications
0
54
1
Order By: Relevance
“…7 Indeed, many trials assessing the effects of probiotics (including using different species of microorganisms) as preventive or therapeutic options for a range of diseases have been conducted and published. 2,5 Consequently, a considerable amount of published data is currently available through MEDLINE. Corroborating this, a search in this database carried out on July 26, 2017, using the MeSH (medical subheading) term probiotics, retrieved 12,370 records, which corresponded to an increase of 278% in the number of records over the last ten years (from December 2007 to July 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Indeed, many trials assessing the effects of probiotics (including using different species of microorganisms) as preventive or therapeutic options for a range of diseases have been conducted and published. 2,5 Consequently, a considerable amount of published data is currently available through MEDLINE. Corroborating this, a search in this database carried out on July 26, 2017, using the MeSH (medical subheading) term probiotics, retrieved 12,370 records, which corresponded to an increase of 278% in the number of records over the last ten years (from December 2007 to July 2017).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Some research has shown that use of probiotics can confer some health benefits, such as treatment for diarrheal disease, prevention of systemic infections and other effects. 2,5 The 2001 definition from the World Health Organization (WHO) states that probiotics are "live microorganisms which, when administered in adequate amounts, confer a health benefit on the host". 6 They are currently presented by media sources as an attractive health promotion method that prevents or cures a range of clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed inconsistent results that were not necessarily adjusted for the type of feeding [27][28][29][30]. A meta-analysis of 15 studies including 3751 infants <32 weeks and <1500 g birth weight demonstrated no significant effects of probiotics on weight gain [31]. In comparison to our cohort, the gestational age in this pooled study cohort analysis was higher while mean weight gain/day was lower (16 g/day vs. 21 g/day) indicating that the effects of probiotics are context sensitive.…”
Section: Discussionmentioning
confidence: 98%
“…In a review on the effects of a variety of immunonutrients in the prevention of necrotizing enterocolitis [35], the authors gathered sufficient data supporting supplementation of infant formulae with probiotics. Several meta-analyses combined these randomized controlled trials and observational studies demonstrated that the use of probiotics was beneficial for the prevention of severe necrotizing enterocolitis, late-onset sepsis, and all-cause mortality in very-low-birth-weight infants, as well as the time to achieve full enteral feeding in preterm infants [36][37][38]. By contrast, no differences were observed in a multicenter study involving 1315 preterm newborns fed with a hydrolyzed formula supplemented and nonsupplemented with the probiotic Bifidobacterium breve BBG-001 [39]; the results of this trial provide no evidence of benefit of this probiotic intervention in reducing late-onset sepsis and necrotizing enterocolitis or death.…”
Section: Prevention and Treatment Of Infant Disordersmentioning
confidence: 99%